Answer:
Option C is right answer
Step-by-step explanation:
We have in coordinate geometry a straight line in slope intercept form as
y = mx+c
where m is the slope and c is the y intercept
There are special lines when m=0 and m = infinity.
When a line is parallel to y axis, it has slope = tan90 = infinity.
Hence line will have equation of the form x = a for some a.
Since the line passes through (3,2) we can find a using this.
Substitute x value to get 3 = x
Hence equation of the line is x =3
Answer:
X=3
Step-by-step explanation:
Anyone good with Literal Expressions?
Answer:
[tex]\boxed{F=\dfrac{9}{5}c+32}[/tex]
Step-by-step explanation:
[tex]\dfrac{5(F-32)}{9}=c\qquad\text{multiply both sides by 9}\\\\5(F-32)=9c\qquad\text{divide both sides by 5}\\\\F-32=\dfrac{9}{5}c\qquad\text{add 32 to both sides}\\\\\boxed{F=\dfrac{9}{5}c+32}[/tex]
A student bought a juice pouch for $2.50 and three bags of chips the total cost was $5.05 right and solve an equation to determine the cost of a bag of chips, c
The total amount of the purchase was ...
... $2.50 + 3c = $5.05
This equation can be solved by subtracting 2.50 and dividing by 3. Both these operations are done to both sides of the equation in accordance with the rules of equality.
... 3c = $2.55
... c = $0.85
The cost of a bag of chips was $0.85.
The cost of a bag of chips can be found by subtracting the juice price from the total cost and then dividing by the number of chip bags. This gives us an answer of $0.85 per bag.
Explanation:To solve this problem, we need to subtract the cost of the juice from the total cost, then divide that answer by the total number of chip bags bought to find the cost of one bag. First, we subtract the juice price ($2.50) from the total spent ($5.05), which gives us $2.55. This is the total cost of the chips. Then, we divide that $2.55 by the number of chip bags bought (which is three) to find the cost of one bag. This can be represented by the equation: c = (total cost - juice price) / number of chip bags, or c = ($5.05 - $2.50) / 3. Calculating this, we find that c equals $0.85, so a bag of chips costs $0.85.
Learn more about Equation Solving here:https://brainly.com/question/18262581
#SPJ3
What is another way to name ∠QRS ? Select each correct answer. ∠R ∠S ∠Q ∠QSR ∠SRQ ∠RSQ
<SRQ Because if you go any other way other than its opppsite you would get a different angle.
Another way to name ∠QRS is ∠SRQ as R is the vertex of the angle.
What is a vertex?A vertex is a common endpoint between two rays that forms an angle.
We know when an angle is represented by three letters the vertex of the angle is the middle letter.
∴ Another name ∠for QRS is ∠SRQ because here R is the vertex of the angle and we can not place R in the first or the third place as it would completely change the vertex of the angle which are not the same angles, of Ofcourse their measure can be same but they are different.
learn more about vertex here :
https://brainly.com/question/12563262
#SPJ2
How do I get the revised bill rate ?
The initial pay rate is $16.00. It is also mentioned that the price is marked up by 78.7%. It means that the prices are increased by 78.7%. Also, there is a profit of 10% too. So, the pay rates after mark up will be
$16.00 + (78.7% of 16.00)
= $16.00 + $12.592
=$28.592
And the pay rates after estimated profit is
$28.592 + (10% of $28.592)
= $28.592 + $2.8592
= $31.4512
Hence, the revised bill rate, rounded to the nearest cent is $31.45.
Solve the literal equation |ax+b|=c for x.
Try this solution; note, this way is not the shortest one.
The solutions for the modular equation are:
[tex]x = \frac{c - b}{a}[/tex] or [tex]x = -\frac{c + b}{a}[/tex]
-----------------------
A modular equation |f(x)| = a means that:
[tex]f(x) = a[/tex] or [tex]f(x) = -a[/tex]
-----------------------
The equation given is:
[tex]|ax + b| = c[/tex]
Which means that:
[tex]ax + b = c[/tex]
[tex]ax = c - b[/tex]
[tex]x = \frac{c - b}{a}[/tex]
Or
[tex]ax + b = -c[/tex]
[tex]ax = -c - b[/tex]
[tex]ax = -(c+b)[/tex]
[tex]x = -\frac{c + b}{a}[/tex]
The solutions are [tex]x = \frac{c - b}{a}[/tex] or [tex]x = -\frac{c + b}{a}[/tex]
A similar problem is given at https://brainly.com/question/5123313
Need help, thanks. :)
Answer:
f(2) = 0
Step-by-step explanation:
Plug x = 2 into the formula for f(x):-
f(2) = 2(2) - 4
= 4 - 4
= 0
f(2) = 0
substitute x = 2 into f(x)
f(2) = (2 × 2 ) - 4 = 4 - 4 = 0
Check out the attachment
The graph of the tangent function approaches vertical asymptotes at x=±π/2. The inverse function will have horizontal asymptotes of y=±π/2. The only viable choice among your graphs is ...
... Graph C
_____
The graph of the inverse of a function is the function's graph with the x- and y-coordinates swapped. Essentially, the graph is reflected across the line y=x. The graph of the tangent function has a vertical aspect. Its inverse has a horizontal aspect.
Please I need your help desperately what is the area of this triangle? See attached image thank you so much
To find the area of the given traingle we have to draw perpendicular from point 'J' which meets the x axis at point (2,0) and let us named it 'P'.
As we know that area of triangle is
[tex] = \frac{1}{2}\times b \times h [\tex]
Here base 'b' will be LK and height 'h' will be JP
Here,
LK= 4 units JP=4 units
Area ={1}{2} *(4)*(4)
On solving the equation we get,
Area=8 Sq units
Can anyone transform a vertex form equation into a standard form?
y= -0.3(x-0)^2+3
If you can show work.
the standard form of a quadratic is : y = ax² + bx + c : (a ≠ 0 )
note that (x - 0 )² = x²
distributing by - 0.3 gives
y= - 0.3x² + 3 ← in standard form
with a = - 0.3, b = 0 and c = 3
To get the color dove-white, Ken mixed black paint and white paint in a ratio of 5:3. He used 20 gallons of black paint. How much white paint did he use?
12 gallons of white paint
divide 20 gallons by 5 to obtain 1 part of the ratio
[tex]\frac{20}{5}[/tex] = 4 gallons ← 1 part
white paint = 3 × 4 = 12 gallons ← 3 parts
- 2/3 + (3/4 + 5/3)
The commutative property of addition lets you rearrange this to
(3/4 +5/3) - 2/3
The associative property of addition lets you regroup this to
3/4 + (5/3 -2/3)
= 3/4 + 3/3
= 1 3/4 . . . . take your pick of the final form
= 7/4
= 1.75
Find the unknown length of y. Please help ASAP!!!!!!!! :(
We assume the slope is a constant, so the rise is proportional to the run.
... y/(4 ft) = (31 ft)/(3 ft)
... y = (4/3)·(31 ft)
... y = 41 1/3 ft = 41 ft 4 in
Which of the following graphs represents a function that has a positive leading coefficient? Check all that apply.
Alright, so i'm looking at the graphs and i'm seeing B as an answer, Probably not A. C and D are confusing,
In the end, i'd say B and D.
If i'm wrong, please tell me.
The correct answers are (B), (C), and (D).
(C) is pretty straight forward. The graph resembles the graph of a quadratic function that us concave upwards. A quadratic function, and functions with an even degree like [tex]x^4, x^6[/tex] will be concave upwards if the leading term is positive.
For function with an odd degree such as [tex]x^3, x^5[/tex] will be mostly negative on the side of the negative x axis and positive on the side of the positive x-axis if the leading coefficient is positive. A cubic function with a positive leading term will be negative on the side of the negative x-axis for large negative numbers and positive on the side of the positive x-axis for large positive numbers. From this explaination we can gather that (B) and (D) are also correct .
The correct options are (B),(C) and (D).
Pls help will mark brainliest
4x+2y=6
x-3y=5
SOLVE BY ELIMINATION METHOD PLS
Answer:
y=-1
Step-by-step explanation:
The first step to solving this problem is to write it out like this-->
4x+2y=6
x-3y=5
Next you want to eliminate the X's or the Y's, I chose to elininate the X's-->
4x+2y=6
-4(x-3y=5) [You MUST distribute the -4 to each of the numbers in the equation]
Then you get--->
4x+2y=6
-4x+12y=-20 Then you add them top to bottom--->
0x+14y=-14 [At this point you dont have to write the X]Next you solve for y-->
14y=-14 Divide both sides by 14, in order to get the y by itself-->
y=-1 And theres your answer hope it helps :D
we have the 2 equations
4x + 2y = 6 → (1)
x - 3y = 5 → (2)
multiply (2) by 4
4x - 12y = 20 → (3)
(3) - (1) to eliminate the terms in x
- 14y = 14 ( divide both sides by - 14 )
y = - 1
substitute y = - 1 into (1) and solve for x
4x - 2 = 6 ) add 2 to both sides )
4x = 8 ( divide both sides by 4 )
x = 2
solution is x = 2, y = - 1
At the annual dog show chantel noticed that there were 3 more scotties than schnauzers. She also realized that the number of wirehaired terriers was 5 less than the number of schnauzers. If there were 78 dogs in all ( counting schnauzers scotties and terriers) how many schnauzers were there? Write and solve equation
x + x - 3 + 2x - 3 = 78
4x = 84
x = 21
Answer: 21 Schnauzers.
Trish plans to sell off 40% of her fast food restraunt business. If the business has been appraised for 350,000 dollars how much money does she expect to raise
40% of $350, 000
40% = [tex]\frac{40}{100}[/tex] = 0.4, hence
expected amount = 0.4 × $350, 000 = $140, 000
Many medications are determined by the weight of the patient in kilograms. When a patient’s weight is measured in pounds, the doctor must then convert the weight to kilograms. The table shows conversions for common units of weight.
Answer:
70.2
Step-by-step explanation:
Multiply the weight in pounds by the conversion factor.
[tex]156\,lb\times\dfrac{0.45\,kg}{1\, lb}=70.2\,kg[/tex]
Answer:
70.2 kilograms
Step-by-step explanation:
In order to calculate this you just have to do a rule of three, where you use the equivalence of the pounds by the kilograms, in the table you see that 1 pound equals .45 kilograms, so you use that for your equivalence:
[tex]\frac{1pound}{.45kilograms}= \frac{156 pounds}{x}[/tex]
[tex]x=\frac{165*.45}{1 pound}[/tex]
[tex]x=70.2 kilos[/tex]
So we know that the patient weights 70,2 kilograms.
Daniela bought a car for $24,000. Each year the value of the car decreases by $1750. a. Write a function that shows the value of the car after y years.
I hope this might be able to help you.
Since the value of the car slowly decreases each year and each year is represented by y, the function is 24,000-1750y=f(x).
In triangle ΔABC, ∠C is a right angle and CD is the height to AB . Find the angles in ΔCBD and ΔCAD if: Chapter Reference a m∠A = 20° Answer: m∠CDB = m∠CBD = m∠BCD = m∠CDA = m∠ CAD= m∠ACD =
In triangle ABC, when ∠A = 20°, then ∠B = 70°, ∠C = 90°. In triangle CAD, when ∠CAD = 20° and ∠CDA = 90°, ∠ACD = 70°. In triangle CBD, with ∠CBD = 90° and ∠BCD = 70°, ∠CDB = 20°.
Explanation:In triangle ΔABC, ∠C is a right angle and CD is the height to AB. Considering ∠A = 20°, by the angles sum property of a triangle, ∠B = 180° - ∠A - ∠C = 180° - 20° - 90° = 70°.
Moving on to triangle ΔCAD, this is a right triangle with ∠CDA=90°. ∠CAD is given as 20° (the same as ∠A of triangle ΔABC). Therefore, ∠ACD = 180° - ∠CAD - ∠CDA= 180° - 20° - 90° = 70°.
For triangle ΔCBD, ∠CBD is 90°, and ∠BCD corresponds to ∠B of triangle ΔABC, which we've determined as 70°. Hence, ∠CDB = 180° - ∠CBD - ∠BCD = 180° - 90° - 70° = 20°.
Learn more about Triangle Angle Calculation here:https://brainly.com/question/28144214
#SPJ12
In triangle ΔCBD, the angles are: m∠CDB = m∠CBD = 90° and m∠BCD = 90°. In triangle ΔCAD, the angles are: m∠CDA = 70° and m∠CAD = 70°. Finally, m∠ACD = 40°.
Explanation:In triangle ΔCBD, since ∠C is a right angle, ∠CBD = 90° and ∠BCD = 90°.
In triangle ΔCAD, using the fact that the sum of angles in a triangle is 180°, we can find that ∠CDA = 90° - ∠CBD = 90° - 20° = 70°.
Similarly, ∠CAD = 90° - ∠BCD = 90° - 20° = 70°.
Finally, since ∠CDA = ∠CAD, ∠ACD = 180° - ∠CDA - ∠CAD
= 180° - 70° - 70°
= 40°.
Learn more about Angles in triangles here:https://brainly.com/question/22262639
#SPJ12
Valerie wants to take out a discount loan of $569. The rate is 4.5% for 250 days. How much interest will she pay? (Be sure to round the time to the nearest hundredth.
The interest is computed from
... I = Prt
where P is the principal amount ($569), r is the rate (0.045) and t is the time in years (250/360).
... I = $569×0.045×250/360 ≈ $17.78
Please note that time is not rounded. Rather, the exact value (25/36) is used in the calculation. The only rounding of any number is done at the end, where the amount is rounded to the nearest cent. (Your text authors should know this.)
_____
If you follow the problem instructions (which Valerie's lender will not do), the interest is calculated as ...
... t = 250/360 = 0.6944444... ≈ 0.69 . . . . years
... I = $569×0.045×0.69 ≈ $17.67
_____
Note the rounding of intermediate numbers (time) introduces an error of about $0.11 in the answer.
Answer:$17.41 (A+)
Step-by-step explanation:
I need help with number 2 please !!
The price of 1 share of stock fell $4 every day for 3 straight days. How did the price of the stock change over these 3 days.
Answer:
The price over three days fell linearly
Step-by-step explanation:
s = stock
s = -4x
s = -4(3)
s = -12
The stock decreased by 12 dollars over 3 days.
Answer: -12
Step-by-step explanation:Hello!I hope you are having a good day or evening and I hope this helps :) !!
the box part of the box plot contains all the values between which numbers?
between 27 and 36 and between 37 and 40
between 32 and 36
between 32 and 37
between 27 and 32 and between 37 and 40
The left end of the box is at 32; the right end is at 37. The box part of the plot contains all the values ...
... between 32 and 37.
Answer:
The correct option is 3.
Step-by-step explanation:
From the given box plot it is clear that
1. The left end point of the line is 27. So, the minimum value of the data is 27.
2. The left end of the box is 32. It means the first quartile of the data is 32.
3. The line inside the box represents the median. So the median of the data is 36.
4. The right end of the box is 37. It means the third quartile of the data is 37.
5. The right end point of the line is 40. So, the maximum value of the data is 40.
It means the box part of the box plot contains all the values between 32 and 37.
Therefore the correct option is 3.
At 3:00 p.m., Jasmine leaves her house and drives north to her parent’s home. She arrives at 6:00 p.m. Also leaving at 3:00 p.m. from Jasmine’s house is her friend Jewel who leaves and drives south to her parent’s home. She arrives at 5:00 p.m. The driving distance between both parents’ homes is 300 mi. Jasmine and Jewel drove at the same speed. What was their speed? *
I think you need to think about the problem carefully. My guess is 1,that's my guess. sorry i couldn't give an accurate answer or you divide 300 by 5
Answer:
60
Step-by-step explanation:
plz help for brainlest
2. A model rocket is launched from the ground with an initial velocity of 288 ft/sec.
c. How long will it take the rocket to reach its maximum height? Show all work in the space provided.
d. Assume the model rocket’s parachute failed to deploy and the rocket fell back to the ground. How long would it take the rocket to return to Earth from the time it was launched? Show all work in the space provided.
2c. We assume that the equations for ballistic motion in a vacuum apply, and the rate of downward acceleration is 32 ft/s². Then it will take ...
... (288 ft/s)/(32 ft/s²) = 9 s
for the rocket to reach its maximum height (its vertical velocity to decrease to zero).
2d. The trip down takes the same amount of time as the trip up, so the round trip time is ...
... (9 s)×2 = 18
_____
More ExplanationThe acceleration due to gravity decreases the vertical velocity by the same amount (32 ft/s) each second. An equation for that might be ...
... v = 288 -32t
When the vertical velocity is zero, the rocket is no longer going up. It has reached its maximum height. Then the equation for that looks like ...
... 0 = 288 -32t
... 32t = 288
... t = 288/32 = 9 . . . . . compare to the solution above
After 9 seconds, the rocket reaches its maximum height.
___
Simplifying the description of free-fall is a little harder. In physics terms, the potential energy the rocket has at its maximum height all gets converted to kinetic energy on the way down. At impact with the ground, the kinetic energy is the same as it was when the rocket was launched. That is, its velocity is 288 ft/s earthward at impact. The above equation for velocity still applies, but now we're solving for v = -288.
... -288 = 288 -32t
... -576 = -32t
... 576/32 = t = 18 . . . . . twice the time it took to reach maximum height.
The round trip takes 18 seconds.
a moving truck charges $250 to rent a truck and $0.40 for each mile driven. mr.lee paid a total of $314. which equation can be used to find m, the number of miles he drove the moving truck?
The sales volume for an online bookstore was 432 books in the first week. Then due to the new policy of tax for on-line shopping, the sales volume dropped to 297 books at the second week. By what percent did the sales volume go down?
The volume drop is 432-297= 135
135 books is a fraction 135/432 of the original volume 432. That is (x100): 31.25%
So the sales went down by 31.25%
31.25 percent of sales go down in second week as compared to first week.
What is percentage?Percentage is defined as a given part or amount in every hundred. It is a fraction with 100 as the denominator and is represented by the symbol "%".
Given that, the sales volume for an online bookstore was 432 books in the first week.
Then due to the new policy of tax for on-line shopping, the sales volume dropped to 297 books at the second week.
Percentage dropped= 297/432 ×100
= 0.6875×100
= 68.75%
Now, 100-68.75=31.25%
Therefore, 31.25 percent of sales go down in second week as compared to first week.
To learn more about the percentage visit:
brainly.com/question/24159063.
#SPJ3
if P(a)=0.60 and P(b)=0.30, then a and b are independent events if
Answer: [tex]\text{P(A or B)}=0.90[/tex]
[tex]\text{P(A and B)}=0.18[/tex]
Step-by-step explanation:
Given : P(A)=0.60 and P(B)=0.30
We will say A and B are independent events if :
[tex]\text{P(A or B)=P(A)+P(B)}\\\\=0.60+0.30=0.90[/tex]
[tex]\text{P(A and B)=P(A) x P(B)}\\\\=0.60\times0.30=0.18[/tex]
Thus , A and B are independent events if :
[tex]\text{P(A or B)}=0.90[/tex]
[tex]\text{P(A and B)}=0.18[/tex]
Answer: P( A and B)= 0.18
1. Refer to the equation 2x − 6y = 12.
(a) Create a table of values for at least 4 points. Show your work.
(b) Use the table of values to graph the line. Use a straightedge or ruler to draw the line.
Answer:
Answer:
x 6 0 3 -3
y 0 -2 -1 -3
Step-by-step explanation:
We substitute x value in the equation and find y.
When x =0, -6y = 12 or y =-2
Likewise all pairs are found out.
Similarly put y =0: x = 6
When x =3, 2(3)-6y =12 :y =-1
When x=-3, 2(-3)-6y=12 or y = -3
Plot these on a graph and join the line.
Graph is attached below:
a. 2x-6y=12: y = (12-2x)/6.
b. Graph the line using (0,2) and (3,0).
(a) To create a table of values for at least 4 points, we can solve the equation for y in terms of x:
y = (12 - 2x) / 6
We can then choose different values for x and plug them into the equation to find the corresponding y values.
Here is a table of values for at least 4 points:
x y
0 2
3 0
-3 4
6 -2
(b) To graph the line, we can use the two points from the table of values that are closest to each other.
In this case, we will use the points (0, 2) and (3, 0).
First, plot the two points on the coordinate plane.
Then, use a straightedge or ruler to draw a line that passes through both points.
Here is the graph of the line 2x − 6y = 12:
For similar question on Graph the line.
https://brainly.com/question/19040584
#SPJ3
What is the value of y in the solution to the following system of linear equations?
2x+2=y
2y=5x-1
A) 3
B) 5
C) 8
D) 12
ANSWER
[tex]y=12[/tex]
EXPLANATION
One way is to make x the subject in one equation and substitute into the other.
[tex]2x+2=y[/tex]
[tex]\Rightarrow 2x=y-2[/tex]
[tex]\Rightarrow x=\frac{y}{2}-1--(1)[/tex]
The second equation is
[tex]2y=5x-1--(2)[/tex]
Let us put equation 1 in 2
[tex]\Rightarrow 2y=5(\frac{y}{2}-1)-1[/tex]
[tex]\Rightarrow 2y=\frac{5y}{2}-5-1[/tex]
[tex]\Rightarrow 2y=\frac{5y}{2}-6[/tex]
Multiplying through by 2 gives;
[tex]\Rightarrow 4y=5y-12[/tex]
[tex]\Rightarrow 4y-5y=-12[/tex]
[tex]\Rightarrow -y=-12[/tex]
[tex]\Rightarrow y=12[/tex]
D
given the 2 equations
2x + 2 = y → (1)
2y = 5x - 1 → (2)
Substitute y = 2x + 2 into (2)
2(2x + 2) = 5x - 1
4x + 4 = 5x - 1 ( subtract 5x from both sides )
- x + 4 = = - 1 ( subtract 4 from both sides )
- x = - 5 ( multiply through by - 1 )
x = 5
substitute x = 5 into (1)
y = (2 × 5 ) + 2 = 10 + 2 = 12 → D